Mencintai Alam dalam Naungan Yang Ilahi: Reinterpretasi Konsep Uti-Frui Agustinus dengan Konsep Seva dan Svarupa - Atmoko, Ricky (Asosiasi Teolog Indonesia, 2023)
Evangelical Christianity’s concern for nature generally follows a dualistic, utilitarian influence that can be traced back to the thought of Augustine. To escape the trap of dualism, I reinterpret the Augustinian dyad of uti (means or use) and frui (enjoyment or delight) using the Hindu notions of seva (selflessness) and svarupa (true form). In doing so, I construct the posture of loving nature from within the divine auspices—namely, to love creation in the shade of God. I employ the reinterpretative comparative theology methodology of Catherine Cornille, which makes one concept from a given religion more understandable by means of the context of another. First, the Hindu notion of svarupa can transpose the dualistic tendency of frui from being directed “to” the divine auspices of God’s being towards the non-dualistic sense of being “within” the divine shade. As such, svarupa is vital for my reinterpretation of frui. Second, the Hindu notion of seva retrieves the meaning of uti from falling into a utilitarian (or, worse still, consequentialist) mode of relating to nature without love. Likewise, I find seva helpful to inform my reinterpretation of uti. By understanding the Augustinian uti-frui binary through seva and svarupa, I propose to develop a non-dichotomous, non-utilitarian comparative environmental paradigm. Moving beyond a God-nature dualism helps Christians to see God’s love in the material world, just as taking a non-utilitarian view helps us to be concerned with the long-term impact of human actions on nature.